Model Pendampingan Guru terhadap Kemampuan Membaca Anak (Studi Kasus di Raudlatul Athfal Manbaul Falah Sidorejo, Pamotan-Rembang) - yuliatun, yuliatun (PIAUD Universitas Islam Negeri Sunan Kudus, 2015)
Young children need a variety of fun activities and in accordance with the character development. Potential Capacity of reading early childhood is very necessary to be developed through various activities are games and also contains an element of learning. This paper aims to describe a model mentoring of teachers to early childhood reading ability. The author argues the results of research on the area of research in early childhood institutions TK / RA Manbaul Falah Sidorejo Pamotan Rembang as a case study of early childhood learning activities in reading membelajarkan activity on students. With descriptive method qualitative and psychological approach, the study found some things that the underlying model of early childhood assistance in developing reading skills, including writing and arithmetic. As a result, that model of mentoring teachers to early childhood literacy refers to two things, namely the realization that every child has the potential ability to read early and that the environment sagat need to explore and develop. The second thing that will be a reference for early childhood teachers in designing a model of mentoring.